1986
DOI: 10.1136/bmj.292.6524.870
|View full text |Cite
|
Sign up to set email alerts
|

The "five minute" consultation: effect of time constraint on clinical content and patient satisfaction.

Abstract: An experiment was carried out in which patients who were seeking appointments for a consultation in a general practice in south London attended consulting sessions booked at 5, 7.5, or 10 minute intervals. The particular session that the patient attended was determined non-systematically. The clinical content of the consultation was recorded on an encounter sheet and on audio-tape. At the end of each consultation patients were invited to complete a questionnaire designed to measure satisfaction with the consul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(92 citation statements)
references
References 0 publications
1
76
0
4
Order By: Relevance
“…1 Prior studies have found that more time spent with patients may improve patient satisfaction, patient education, and clinical outcomes, and reduce inappropriate prescribing. [19][20][21][22] In the wake of the 2003 and 2011 work hours limitations, the proportion and absolute amount of time spent in direct patient care has dropped in both Fletcher's study 14 and this study. As a result, the total time residents can expect to spend learning from patients appears to have decreased, which may affect the quality of the patient-physician relationship and the quality of care delivered.…”
Section: Discussionmentioning
confidence: 71%
“…1 Prior studies have found that more time spent with patients may improve patient satisfaction, patient education, and clinical outcomes, and reduce inappropriate prescribing. [19][20][21][22] In the wake of the 2003 and 2011 work hours limitations, the proportion and absolute amount of time spent in direct patient care has dropped in both Fletcher's study 14 and this study. As a result, the total time residents can expect to spend learning from patients appears to have decreased, which may affect the quality of the patient-physician relationship and the quality of care delivered.…”
Section: Discussionmentioning
confidence: 71%
“…27,28,49 Physicians and patients believe visit duration is important for quality of care. 50,51 Longer visits are associated with higher communication quality, 52 greater ease of discussing problems, 53,54 and more participatory decision-making 54 by patients. Constraining visit length to reduce health-care costs may place minorities and patients with suboptimal disease control at higher risk for poorer quality communication and disease outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no real evidence that longer is better, some benefits of longer consultations have been mentioned. Research showed that in longer consultations doctors prescribe less [4,5], listen better to their patients, identify more problems, explore more psychosocial problems and provide more health promotion [3,6]. When we take these measures as a proxy for quality, longer consultations seem to be better [5,7,8].…”
Section: Introductionmentioning
confidence: 99%